TUVAN KHOOMEI IN ENSEMBLE PERFORMANCE BASED ON THE WORK OF THE FOLK GROUP «ALASH» (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article describes the current state of ensemble performance in Tuvan throatsinging khoomei and reveals the role and place of the folklore group «Alash» in the musical arena of Tuva and Russia. The novelty and relevance of the chosen topic is beyond doubt against the background of growing scientific and commercial interest in the art of khoomei, the rapid development of performing practices, the competence and competitiveness of Tuvan folklore groups in World music, and the abundance of audiovisual materials on the Internet. The purpose of the study is to reveal the role and place of Tuvan folklore groups in the musical arena of the region and the country using the example of the Alash ensemble. When writing the article, the author adhered to the methodological approaches of cultural studies and ethnomusicology. As a result of the research, the author noted: 1) the demand for folklore groups of Tuva, based on the common properties of traditional culture and genres of modern music, in the world folk music market; 2) the formation of a positive image and enrichment of culture of ethnic peoples of Russia.
Keywords: Tuvan khoomei, khoomei ensembles, «Alash» group, form of existence, performing arts, folklore, repertoire, music industry.